Feasibility of Age Estimation from Exfoliated Buccal Mucosal Cells in Adults: A Cytomorphometric Study - Madhan, B; Toi, P Ch; Krishnan, B (Journal of Indian Academy of Forensic Medicine, 2024)
This study aimed to evaluate the age and gender-related cytomorphometric changes in the buccal mucosal cells of Indian adults and the  feasibility of age estimation from them. Exfoliative cytology smears were collected from the clinically normal buccal mucosa of 90  individuals (30 in age groups of 21-30, 31-40, and 41-50 years). They were fixed in 95% alcohol and stained with the Papanicolaou  technique. The Cytoplasmic Area (CA) and Nuclear Area (NA) in square micrometers and the Nuclear area: Cytoplasmic area Ratio  (NCR) were estimated for each individual by averaging the measurements from 100 clear and unfolded cells. The age and sex-based  intergroup comparisons were made with Analysis of Variance and Independent samples T-test (or their non-parametric equivalents),  respectively. Pearson and Point Biserial correlations were used to assess the association of NA, CA, and NCR with age and gender,  respectively. The cytoplasmic area showed a statistically significant difference (p=.04) between 21-30 years (2572.34 ± 516.54) and 31-40  years (2230.15 ± 516.12). NA and NCR did not differ between age groups. While females (0.030 ± 0.007) showed a higher NCR than  males (0.026 ± 0.005, p=.009), no sexual dimorphism was noted for CA and NA. No statistically significant correlations were found  between age and CA, NA, or NCR. Though the buccal mucosal cells from adults exhibited some age and gender-related cytomorphometric  changes, it is not feasible to predict the chronologic age of an individual from them.
Keywords: Age estimation; Cytomorphometrics; Exfoliative cytology